Reconstruction of full thickness defects on the scalp with artificial dermal regeneration template: Analysis of long-term results in 68 cases - Benecke, Johannes; Koenen, Wolfgang; Mager, Lisa Marie; Weina, Kasia; Klemke, Claus-Detlev; Felcht, Moritz; Faulhaber, Jörg (Dermatologic surgery, 2021)
BACKGROUND - Artificial skin substitute templates have been shown to be a reliable solution for the reconstruction of large scalp defects with exposed skull bone, but there is a lack of long-term data. OBJECTIVE - The aim of this retrospective study was to investigate the long-term outcome of the procedure in a large cohort of 68 cases. MATERIALS AND METHODS - In total, 58 patients with 68 full thickness scalp defects with exposed skull bone, were included. Mean follow-up time was 24 (±19) months. RESULTS - The mean size of the defects was 63 (±54) cm2. During the follow-up period, no local recurrences occurred. Complications were observed in 13% of the cases including template necrosis (4%), infections (4%), ulcerations (3%), and autograft necrosis (2%). During the final follow-up, 26 patients had died due to internal diseases not associated with the surgery. Cosmetic results were rated good by the patients and an independent observer. CONCLUSION - The use of a dermal regeneration template for the reconstruction of large, full thickness defects of the scalp with exposed skull bone is a reliable method regarding the complication rate, safety of the procedure, and cosmetic outcome. Limitations of this study are the retrospective and single center design.
Gesehen am 01.07.2021